Primary oxidative phosphorylation defects lead to perturbations in the human B cell repertoire - Gordon-Lipkin, Eliza M.; Banerjee, Payal; Franco, Jose Luis Marin; Tarasenko, Tatiana; Kruk, Shannon; Thompson, Elizabeth; Gildea, Derek E.; Zhang, Suiyuan; Wolfsberg, Tyra G.; , NISC Comparative Sequencing Program; Flegel, Willy A.; McGuire, Peter J. (Frontiers in Immunology, 2023)
The majority of studies on oxidative phosphorylation in immune cells have been performed in mouse models, necessitating human translation. To understand the impact of oxidative phosphorylation (OXPHOS) deficiency on human immunity, we studied children with primary mitochondrial disease (MtD). Using scRNAseq analysis of peripheral blood mononuclear cells, we found marked reductions in select populations involved in the humoral immune response, especially antigen presenting cells, B cell and plasma populations, with sparing of T cell populations. MTRNR2L8, a marker of bioenergetic stress, was significantly elevated in populations that were most depleted. mir4485, a miRNA contained in the intron of MTRNR2L8, was co-expressed. Knockdown studies of mir4485 demonstrated its role in promoting survival by modulating apoptosis. To determine the functional consequences of our findings on humoral immunity, we studied the antiviral antibody repertoire in children with MtD and controls using phage display and immunoprecipitation sequencing. Despite similar viral exposomes, MtD displayed antiviral antibodies with less robust fold changes and limited polyclonality. Overall, we show that children with MtD display perturbations in the B cell repertoire which may impact humoral immunity and the ability to clear viral infections.